Assessing the impact of genotype-by-environment interactions on agronomic traits in elite cowpea lines across agro-ecologies in Nigeria - Popoola, B.; Ongom, P.O.; Mohammed, S.B.; Togola, A.; Ishaya, D.J.; Bala, G.; Fatokun, C.; Boukar, O. (MDPI, 2024)
The yield of cowpea varieties is affected by environmental variability. Hence, candidate varieties must be tested for yield stability before release. This study assessed the impacts of genotypes, environments, and their interaction on the performance of elite cowpea lines for key adaptive, grain yield, and associated traits across different locations. A total of 42 elite genotypes were evaluated in five Nigerian environments, representing various savanna ecologies, during the 2021 growing season. The experimental design employed was an alpha lattice arrangement, with each genotype replicated three times. The results revealed significant differences among genotypes, environments, and genotype-by-environment interaction (G × E) for most traits, including days to maturity, 100-seed weight, and grain yield. The genotype and genotype-by-environment interaction (GGE) biplot showed G21 (IT14K-2111-2) and G25 (IT15K-2386-1) as the most stable genotypes across the five environments, G41 (IT11K-61-82) was best adapted to Ibadan and Shika, G5 (245-1) was best adapted to Bagauda and Gumel, and G30 (IT16K-2365-1) was best adapted to Bauchi. G21 (IT14K-2111-2) and G25 (IT15K-2386-1) could be recommended across the five test environments, whereas G41 (IT11K-61-82), G30 (IT16K-2365-1), and G5 (245-1) were specific to the adapted environments.